NILAI-NILAI RELIGIUS PADA ASPEK HUBUNGAN MANUSIA DENGAN MANUSIA (HABLUMINANNAS) DALAM NOVEL KARENA AKU MEMILIH-MU KARYA HAMAS SYAHID - Sujoko Sujoko; Rosita Rosita (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research aims to describe religious values which are related to the relationship of humans to humans (habluminannas) in the novel Karena Aku Memilih-Mu by Hamas Syahid. This research is descriptive qualitative. The source of the data is the novel Karena Aku Memilih-Mu by Hamas Syahid. The data is acquired by using documentation technique with content analysis. The result of the research shows that: (1) the aspect of helping each other in a form of handing a help withoud asking, handing a help without differentiating tribe, race, and religion, and working together; (2) the aspect of keeping a promise in the form of secure trust and trustworthy; (3) the aspect of being fair in the form of treating a person equally, and not favoring anyone; (4) the aspect of forgiving in the form of forgiving someone’s mitakes, trying to think positively and forgiving the wrongdoers, and giving sincere apologize. The most dominant aspect of religious values related to humans to humans (Habluminannas) is the aspect of helping each other with the total number of 50 quotes, while while the fewest one is the aspect of being fair with the total number of 7 quotes.